Review of Nursing Interventions to Reduce the Sodium Intake for Patients with Chronic Heart Failure - Wang, Qianyi; Shang, Shuhua; Sun, Jinyu; Sun, Guozhen; Gu, Zejuan (Cardiology and Cardiovascular Medicine, 2019)
This study aimed to systematically evaluate the effect of nursing interventions on reducing dietary sodium intake in patients with chronic heart failure, further to provide insight on the most utilized nursing practices. Only randomized controlled trials on dietary sodium management of nursing interventions were collected from Pubmed, CINAHL, Web of Science, Embase and The Cochrane Library (CENTRAL). Among 515 available studies, a total of 8 ones met the inclusion criteria and were included. The meta-analysis result suggested that nursing interventions could reduce dietary sodium intake in patients with chronic heart failure within 6 months compared with conventional care [SMD (-0.305, 95%CI -0.561, -0.049)]. Considering the sodium levels estimated by the 3-day food record is much lower than those by the 24-hour urinary sodium, it is better to analyze separately to further clarify the effect of nursing interventions. Hence, further meta-analysis results showed that the sodium intake estimated by the 3-day diet record/diary in the experimental group was lower than that in the control group [SMD -0.523, 95%CI (-0.894 to -0.152), P=0.006]. Similarly, the sodium intake in the experimental group was lower than that in the control group by 24-hour urine specimen [WMD -364.318, 95% CI (-603.953 to -124.684), P=0.003]. We concluded that nursing interventions can reduce dietary sodium intake in patients with chronic heart failure in the short term. However, the long-term effects are uncertain, and long-term planned randomized controlled trials in heart failure patients are required to further verify the effect in the future.